Triage of women with ASC-US/LSIL cytology: the added value of implementing an HPV-test - Msomphora, Mbachi Ruth (UiT Norges arktiske universitet, 2015)
Background: Within the Norwegian cervical cancer screening program women were recommended biopsy after three consecutive smears of minor lesions (ASC-US/LSIL) 6-12 months apart until 2005. In 2005 the recommendations for biopsy changed to the 2nd ASC-US/LSIL, if the HPV-test was positive. In this study we determine the outcomes of secondary cervical cancer screening in two time-periods before (1996-1998) and after (2006-2008) implementation of an HPV test. Methods: This study has a historical prospective design by including in retrospect all screening- and follow-up tests for women aged 25 to 69 years old kept by the Department of Clinical Pathology, University Hospital of North Norway. All women with a first ASC-US/LSIL smear in 1996-98 and 2006-08 were identified and compared on outcomes such as proportion of cases resolved within 42 months of index smear and incidence of CIN2+. The Department of Clinical pathology has used an HPV mRNA test (NorChip PreTect HPV-Proofer) since the autumn of 2005 in secondary cervical cancer screening (triage). Results: Over the years January 1st 1991 and December 31st 2010 UNN laboratory processed 635 287 smears. After exclusion criteria, the study population comprised of 1405 women during 1996-1998 (study group A) and 738 women with a valid HPV-test in triage during 2006-2008 (study group B). In these subsets 16.2% (227/1405) in 1996-98 and 18.8% (139/738) in 2006-08 of the women were eligible for colposcopy/biopsy according to national screening recommendations. In 2006-08, when the HPV mRNA test was applied, the mean time to resolve an ASC-US/LSIL was 9.1 months (range 3-41) relative 23.1 months (range 4-42) in 1996-98 (p<0.001). Significantly more cases were solved in study group B, including HPV-testing at 1st follow-up (82.4%) compared to study group A (53.6%) within 42 months of follow-up. The positive predictive value of CIN2+ 52.0% (64/124) in study group B was significantly higher compared to that of study group A 41.7% (68/163), when there was indication for ...